Los vulnerables como locus revelationis: Fenomenología, hermenéutica y teología de la liberación = Abweichender Titel: The Vulnerable as Locus Revelationis : Phenomenology, Hermeneutics and Liberation Theology - Porcel Moreno, Manuel (Cauriensia, 2025)
The aim of this paper is to show how the theology of revelation, from a phenomenological and hermeneutical perspective, can redefine the proposal of liberation theology and the preferential option for the poor in a fuller and more meaningful way. We will try to philosophically ground the preferential option for the poor within the context of Christian revelation - apokalysis -. This will allow us not only to consider the most vulnerable as locus revelationis, but will also enable liberation theology to recalibrate certain political and ethical positions on how to approach concrete actions against poverty in solidarity.